2004
DOI: 10.1007/s00384-003-0577-x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased interstitial cells of Cajal in the sigmoid colon of patients with slow transit constipation

Abstract: Similar distribution of ICC was observed in the normal sigmoid colon of the Chinese. Decreased area of c-kit+ ICC may play an important role in the pathophysiology of STC. It remains to be determined whether the loss of ICC is primary or secondary to another lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…We (Tong et al 2004) and others (He et al 2001;Feldstein et al 2003) have confirmed the discovery of the loss of ICC within a number of human GI motility disorders, including slow transit constipation, diabetic enteropathy, and pseudo-obstruction etc. In several models of ICC injury, the loss of ICC and gut motility is severe, but restoration can take place within weeks.…”
Section: Discussionsupporting
confidence: 53%
“…We (Tong et al 2004) and others (He et al 2001;Feldstein et al 2003) have confirmed the discovery of the loss of ICC within a number of human GI motility disorders, including slow transit constipation, diabetic enteropathy, and pseudo-obstruction etc. In several models of ICC injury, the loss of ICC and gut motility is severe, but restoration can take place within weeks.…”
Section: Discussionsupporting
confidence: 53%
“…108 The etiology of this disorder is poorly understood and recent investigations have focused on neural mechanisms, including a decrease in interstitial cells of Cajal. 109,110 Investigators have also evaluated other potential mechanisms, including proto-oncogenes, tyrosine kinase C, autonomic neuropathy, overexpression of progesterone receptors, infectious agents, autoimmunity, medications, as well as gut hormones. [111][112][113][114][115][116][117][118][119][120] A number of studies suggest that alterations in 5-HT signaling may contribute to the symptoms of chronic constipation, but again, inconsistencies exist among these investigations (Table 2).…”
Section: Chronic Constipationmentioning
confidence: 99%
“…Their findings suggest that excessive and uncoordinated phasic rectal activity may further impede stool transport and contribute to STC [40] .…”
Section: Physiology Of Dysmotilitymentioning
confidence: 99%